The tillage for potato cultivation at an altitude of 1,200 meters above sea level: Best practice in Mekar Setia Farmers Group, West Java - Efrin Firmansyah; Delanisa Nurwahidah Putri (Community Empowerment, 2023)
Potato (Solanum tuberosum L.) is one of the horticultural commodities that is widely consumed by the public. One of the potato-producing areas in West Java is Pangalengan, Bandung Regency. One of the important factors that influence the success of cultivation is the provision of land according to the needs for the growth and development of potato plants. This technical note was made as a means of information regarding technical land management for potato cultivation at an altitude of 1,200 meters above sea level. The methods used to obtain information include observation, interviews, and literature studies. The results of the observation and interview activities show that land preparation for the preparation of potato cultivation is included in conventional land management techniques (maximum tillage). Land preparation activities carried out include loosening the soil, applying dolomite, applying basic fertilizer, applying insecticides, making beds, installing mulch, and making planting holes.